Upaya Kepala Sekolah dalam Meningkatkan Profesionalisme Guru PAI Melalui Merdeka Belajar Di UPT SD Negeri 110 gresik - Muhammad Adam Maulana Al Aqsho; Sholahuddin Al Ayubi; Siti Mufarochah (Jurnal Pendidikan Agama Islam Miazhar, 2022)
Education in the 4.0 revolution era for teachers to apply new innovations and be able to compete for the better with other institutions, especially in the field of Islamic religious education (PAI). Islamic religious education is very closely related to education in general, Islamic religious education aims to increase students' devotion to Allah SWT which is in line with the mission of Islam, namely to enhance moral values so as to achieve akhlakul karimah. So the Indonesian government issued a new curriculum called the independent learning curriculum. With the existence of a new curriculum that supports learning obtained from several factors and obstacles and also what efforts are made by the principal to improve the professionalism of a teacher.